สมบัติเชิงกลของเข็มฉีดยาระดับไมครอนประเภทพอลิเมอร์ที่ดูดซึมได้ - ณภัทร สุขนฤเศรษฐกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Dissolvable microneedles (DMNs) are micron-sized needles that are made from biodegradable polymers. DMNs can be used to deliver drug through skin without pain. DMNs must be able to penetrate into skin, thus mechanical properties are crucial. Here, we studied the effect of maltose on some mechanical properties of DMNs. The DMNs composed of hyaluronic acid and poly(vinyl pyrrolidone) and various concentrations of maltose, were investigated. The resistance compression was determined by Universal Testing Machine. The hardness was evaluated by Microhardness Tester. Ability of DMNs to penetrate into pig skin was monitored. In conclusion, maltose could improve both mechanical parameters of DMNs.